Estimation of nitrous oxide, carbon dioxide and methane emissions from selected rice soils in Malaysia using DNDC model - Gandahi, Rabail (2015)
Greenhouse gases (GHG) such as carbon dioxide (CO2), methane (CH4) and nitrous oxide (N2O) are the main cause of global warming. In Malaysia, all these gases can be assessed through Denitrification and Decomposition (DNDC) model in various agricultural systems. Three soils and agriculture system studied for simulation were located in Kota Bharu (Kelantan) situated between 6°8′N 102°15′E, Alor Setar (Kedah) situated between 06°07'N,l 100°22'E and Selangor, Malaysia situated at 2°43′N 101°57′E. All the three sites have double cropping system in a year. The objectives of these studies were to examine and forecast the agricultural practices involved in N2O, CO2 and CH4 emissions from various rice fields and to utilize the modeling approach to estimate changes in N2O, CO2 and CH4 emissions from rice soils of Malaysia. Through DNDC model, four interacting sub-models: thermal/hydraulic, crop growth, decomposition, and denitrification were simulated. (Rice cultivation is an important source of GHGs that cause global warming. Rice systems contribute over 25% of total global anthropogenic CH4 emissions currently). The model efficiently treats nitrogen inputs from atmospheric deposition, fertilizer use and nitrogen fixation and represents soil inorganic turnover to enable calculation of gas emissions. The farmers of Kelantan, Kedah and Selangor apply 248, 280 and 300 kg N ha-1 year-1,respectively. The model validation was found satisfactory and gave correct simulations when compared with other studies reported elsewhere. In Kelantan,simulated CO2 flux rate was 4392 kg C ha-1, 33.7 N2O kg ha-1 year-1 with -2CH4 flux kg ha-1 year-1. The Global Warming Potential (GWP) for CO2 flux was 16105 kg CO2-eq ha-1, N2O 16403 kg CO2-eq ha-1. However, CH4 was found as sink (-66 kg CO2-eq ha-1). Bulk of all these gases had 32442 kg CO2-eq ha-1 net GWP. In Kedah, the simulated CO2 flux rate was 4675 kg C ha-1 and 15.2 kg N2O ha-1 year-1 recording -3 CH4 flux kg ha-1 year-1. The GWP for CO2 flux was 17141 kg CO2-eq ha-1, N2O 454412 kg CO2-eq ha-1. However, CH4 was found as sink (-92 kg CO2-eq ha-1) and thus, bulk of all these gases had 471460 kg CO2-eq ha-1 net GWP. In Selangor, CO2 flux rate was 1489 kg C ha-1, 152.1 N2O kg ha-1 year-1 with -2 CH4 flux. The GWP for CO2 flux was 5460 kg CO2-eq ha-1 and N2O 74085 kg CO2-eq ha-1. However, CH4 was found as sink (-66 kg CO2-eq ha-1). Bulk of all these gases had 79440 kg CO2-eq ha-1 net GWP. The simulations for field uncertainties were tested with variable nitrogen rates at 20% less than recommended and 20, 40 and 60% more N than recommended along with soil organic carbon (SOC) rates at 4, 3, 2 and 1.93% kg C kg-1 in Kelantan, 2, 3, 4 and 5% SOC rates in Kedah and 2.31, 3, 4 and 5% in Selangor. In all the rice sites, the unit increase in N rate as well as SOC correspondingly increased N2O flux by 10.06, 6.80, 6.51 and 1.16 kg N ha-1. NO flux by 0.76, 3.25, 3.14 and 2.03 kg N ha-1 year-1.N2 flux 17.87, 18.21, 21.75 and 25.22 kg ha-1 year-1. N2O GWP flux rate by 3495.3, 1614.6, 6.3.0 and 499.4. In Kedah, the unit increase in N rate as well as SOC correspondingly increased N2O flux by 0.25, 0.42, 2.51 and 0.96 kg N ha-1, NO flux by 1.04, 1.17, 1.33, 1.51 kg N ha-1 year-1 and N2 flux by 0.12, 0.83, 1.19 and 0.99 kg ha-1 year-1. N2O GWP flux rate by 30.6, 23033, 110302 and 154765. Similarly, in Selangor, the unit increase in N rate as well as SOC correspondingly increased N2O flux by 2.86, 3.83, 7.61 and 1.95 kg N ha-1. NO flux by 5.41, 5.0, 4.39 and 3.78 kg N ha-1 year-1. N2 flux by 5.22, 9.76, 18.46 and 30.44 kg ha-1 year-1. N2O GWP flux rate by 1385.3, 1865.3, 2701.5 and 3411.5. In conclusion, the DNDC model validations were accurate for Malaysian rice. The farmers of these three sites are applying more nitrogen fertilizer against the crop demand corresponding more yearly NH3 volatilization loss and increased fluxes of N2O, NO and N2 in the environment and excess fertilizer leach down in the soil by polluting underground water. In Malaysian rice, the simulated CH4 values were negative indicating it as sink. In these sites, the GWP is also increasing due to elevated CO2, ongoing management practices especially cropping system, straw incorporation, irrigation/flooding and N fertilizer management as well as C storage potential of the soil which is increasing with the passage of time due to left over residues and soil flooding condition. The DNDC, was modified to enhance its capacity of predicting GHG emissions from rice ecosystems. The major modifications focused on simulations of anaerobic biogeochemistry and rice growth as well as parameterization of rice management. The new model was tested for its sensitivities to management alternatives and variations in natural conditions including weather and soil properties. The test results indicated that (1) varying management practices could substantially affect CO2, CH4, or N2O emissions from rice; (2) soil properties affected the impacts of management alternatives on GHG emissions; and (3) the most sensitive management practices or soil factors varied for different GHGs. For estimating GHG emissions under certain management conditions at regional scale, the spatial heterogeneity of soil properties (e.g., texture, SOC content, pH) are the major source of uncertainty.